Health Seeking Behaviour among Undergraduates in the Faculty of Health Sciences and Technology, University of Nigeria Enugu Campus - Okechukwu Odinaka Ajaegbu; Ijendu Ihuarulam Ubochi (Institute of Advanced Engineering and Science, 2016)
Health is essential for social and economic development of any country. Nearly 10 million children in developing countries die each year before reaching the age of five from ailments, mostly pneumonia, diarrhoea, and malaria.The socio-cultural belief about the causation of disease and its curability has direct correlation with the treatment seeking behaviour of an individual.It is in the light of the foregoing that this research was necessitated to investigate various health seeking behavours exhibited by undergraduates in the Faculty of Health Science and Technology. Health Belief Model was used to examine ways people react to health issues. A descriptive survey research design was employed while questionnaire was data collection tool for the study. The study revealed that common illnesses among students are headache and fever. Students generally go to buy drugs from the patent medicine stores when sick. Students will not go to the hospital until they experience pains that they cannot accommodate again. Factors affecting the choice of health care adopted when ill is mostly related to its accessibility, effectiveness and none delay. Finally, while government should be able to provide access to many health care facilities, health promotion and preventive strategies should be reinforced in universities.